The Decline in the Popularity of the Sundanese Language and Culture among Sundanese Ethnic Youth - Serin, Pavel; Kartika, Nyai; Machdalena , Susi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
As Indonesia's second-largest indigenous language, Sundanese plays a pivotal role in communication between Sundanese people. However, today’s young generations of Sundanese do not use the Sundanese language entirely and do not use it either with their friends on campus or with their parents at home. This study tries to examine the decline in the popularity of the Sundanese language among the young Sundanese generations in the capital city of West Java, a centre for the Sundanese ethnic group. Employing a descriptive survey, this study involved a total of 317 participants from a Sundanese ethnic group. The findings confirmed the initial suspicions that the use of the Sundanese language has begun to decline among the young Sundanese generations in Bandung. Among the several factors of this decline are the very intensive interactions via social media by young Sundanese generations with people of different linguistic and cultural backgrounds, causing the limited use of the Sundanese language among them. It is also due to the shift of Bandung to become a multilingual city, a melting pot of people from different backgrounds. This study can hopefully inspire the language education stakeholders in West Java to raise concerns on this issue by strengthening and modifying Sundanese language education and teaching primarily at the school level.